Lactation class affects changes in mother’s knowledge and attitudes and increases breast milk production: study at Pratama Tanjung Clinic, Deli Serdang Regency - Warda, Eliza; Desfauza, Evi; Nurhayati, Ida (BKM Public Health and Community Medicine, 2021)
To reduce the Neonatal Mortality Rate by at least 12 per 1,000 KH in 2030, increasing access and quality of services for newborns is a top priority by preventing malnutrition. Therefore, WHO and UNICEF urge breastfeeding for newborns to last for at least six months. However, breastfeeding is not easy, especially for new mothers. This research purpose is to determine the outcome of lactation class on breast milk production for postpartum mothers. This study method was Quasi-Experimental with a posttest-only control group design to determine the differences in breastfeeding expenditure for post-partum mothers on Day 7 by comparing what was done and not done in the lactation class. The research population was the third trimester’s pregnant women and who gave birth at BPM Tanjung Delitua Deli Serdang Regency from July to October 2019 was taken by purposive sampling. Univariate and Bivariate data analysis used dependent t-test and Independent t-test using SPSS. The results showed an increase in the average respondent's knowledge of 6.15, attitude 19.32, before and after lactation class was carried out, with a value of P = 0.000 and the difference in the average production of ASI 8.79 with a value of p=0.000, weight gain was 3.313 p=0.912 and elimination of infants 0.79 with a p value=0.028 of those who followed and those who did not participate in the lactation class. The implementation of lactation classes increases knowledge, attitudes, and differences in the production of postpartum breast milk and the elimination of babies.